Union Rates and Deformity Correction Using the Hintermann Osteotomy in Type IIb Flatfoot Deformity - Brian P. Gallagher MD; Walter C. Hembree MD; Lew C. Schon MD (Foot & Ankle Orthopaedics, 2020)
Category: Ankle; Hindfoot Introduction/Purpose: Multiple Lateral column lengthening procedures have been described for the correction of the abduction component of stage II flatfoot deformity. The Hintermann osteotomy, although technically difficult, offers powerful lengthening of the lateral column with low risk of violating the articular cartilage of the subtalar joint as compared to the more widely performed Evans osteotomy. This study reports on the radiographic and clinical outcomes of the Hintermann osteotomy performed by a single surgeon. Methods: Patients who underwent reconstruction for stage II flatfoot deformity with a Hintermann lateral column lengthening were restrospectively identified. The talus-1st metatarsal angle, percent talus uncoverage, calcaneal pitch, lateral column length, CC joint subluxation, and distance from CC joint to the osteotomy were measured on pre and postop radiographs. Radiographic union was also assessed. The Kellgren-Lawrence scale was used to assess degenerative changes at the ST, CC, and TN joints. Charts were reviewed for comorbidities, clinical evidence of union, time to protected weightbearing, time to unrestricted weightbearing, signs of peroneal irritation, clinical signs of osteoarthritis progression, and complications. A paired students t test was used to identify differences in radiographic parameters. Results: Twenty-six patients (30 feet) met inclusion criteria. All osteotomies achieved union with only 1 (1/30) instance of delayed union. Average duration before clinical and radiographic union was 12.6 weeks (9-37). The AP Talus-1st metatarsal angle decreased on average of 12.3 degrees (STD 9.1) (p<0.0001). Percent talus uncoverage decreased on average 17.7 percent (STD 11.5%) (p<0.0001). Subluxation at the CC joint was found to increase on average 1.63mm (STD 1.99) (p<0.01). Only 3 patients (10%) had radiographic progression of osteoarthritis at either the CC or ST joint. No patients showed clinical signs of osteoarthritis and none went on to fusion. One patient had lateral hardware pain necessitating plate removal. Conclusion: The Hintermann osteotomy is a powerful tool for lateral column lengthening. In this series there was significant correction of the preoperative abduction deformity with no nonunions. Degenerative changes in the surrounding hindfoot joints were rare. One benefit of the Hintermann osteotomy is its ability to preserve the articular cartilage of the anterior and middle facets.